ANALISIS KEBIJAKAN PUBLIK DALAM PENGENDALIAN PENCEMARAN LINGKUNGAN: PENDEKATAN HUKUM DAN ALTERNATIF SOLUSI DI KOTA PADANG - Zuldani, Irwan; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Environmental pollution is a serious issue faced by Padang City, negatively impacting public health and ecosystems. This article analyzes the public policies implemented for environmental pollution control, emphasizing the legal approaches employed by local government. Through this study, various existing regulations and their effectiveness in reducing pollution levels are identified. Additionally, the article explores alternative solutions that involve community participation, environmentally friendly technologies, and cross-sector collaboration. The analysis results indicate that, despite having an adequate legal framework, challenges in implementation and public awareness remain significant obstacles. Therefore, stronger collaborative efforts between the government, community, and private sector are necessary to achieve more effective pollution control in Padang City.